Life strategies of some long-distance migratory catfish in relation to hydroelectric dams in the Amazon Basin - Barthem, Ronaldo Borges; de Brito Ribeiro, Mauro César Lambert; Petrere Jr., Miguel [UNESP] (Elsevier, 1991)
In this paper, we present evidence that the long-distance migratory catfish Brachyplatystoma filamentosum, B. flavicans, B. vaillantii, Goslinia platynema and Lithodoras dorsalis spawn in the headstreams of the Amazon river and its tributaries and that the estuary of the Amazon is the main nursery ground utilized by their alevins. The impact of hydroelectric dams on their populations are discussed in terms of interruption to fish migration routes up river and to larvae moving down river, provided that the hypothesis above holds. Ways of mitigating the impact are also considered. © 1991.
Keywords: catfish; hydroelectric dam; Brazil, Amazon; South America, Amazonia; Brachyplatystoma; Brachyplatystoma flavicans; Goslinia platynema; Lithodoras dorsalis